The evolution and development of coloniality in hydrozoans. Issue 3 (15th August 2020) - Cartwright, Paulyn; Travert, Matthew K.; Sanders, Steven M.
Abstract: Hydrozoan colonies display a variety of shapes and sizes including encrusting, upright, and pelagic forms. Phylogenetic patterns reveal a complex evolutionary history of these distinct colony forms, as well as colony loss. Within a species, phenotypic variation in colonies as a response to changing environmental cues and resources has been documented. The patterns of branching of colony specific tissue, called stolons in encrusting colonies and stalks in upright colonies, are likely under the control of signaling mechanisms whose changing expression in evolution and development are responsible for the diversity of hydrozoan colony forms. Although mechanisms of polyp development have been well studied, little research has focused on colony development and patterning. In the few studies that investigated mechanisms governing colony patterning, the Wnt signaling pathway has been implicated. The diversity of colony form, evolutionary patterns, and mechanisms of colony variation in Hydrozoa are reviewed here. Abstract : Phylogenetic distribution of distinct colony forms in Hydrozoa. Research Highlights: Hydrozoan colony diversity and mechanisms dictating colony form are reviewed here. Colonies are patterned through branching of stalks and stolons and polyp budding. The Wnt signaling pathway likely plays a key role in colony patterning and evolution.